2015
DOI: 10.1002/ejoc.201500502
|View full text |Cite
|
Sign up to set email alerts
|

Modular Access to Tetrasubstituted Imidazolium Salts through Acid‐Catalyzed Addition of Isocyanides to Propargylamines

Abstract: Propargylamines, prepared through A3‐coupling of primary amines, aldehydes and terminal alkynes, react with isocyanides in an HCl‐catalyzed process to yield tetrasubstituted imidazolium salts. The key step of the mechanism involves the generation of an amidine intermediate, from the isocyanide insertion into the N–H bond of the propargylamine, which in situ evolves by cyclization upon the alkyne moiety. The scope of the process is analyzed and only shows restrictions for aliphatic amines, whereas it is quite g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…As a matter of fact, regioselective cyclization of structurally related substrates such as 2‐alkynyl benzoic acid 26 , 2‐alkynyl benzamides 27 , propargyl ureas 28 , and propargyl guanidines 29 has been extensively studied and conditions have been established for performing either a 5‐ exo ‐dig or a 6‐ endo ‐dig cyclization (Figure ). However, the cyclization of amidine 19 has been far less investigated and to the best of our knowledge, only 5‐ exo ‐dig cyclization leading to imidazole is known . Indeed, in this case, the 5‐ exo ‐dig cyclization furnishes an aromatic compound 16 after facile double‐bond isomerization of the primary cyclization product 30 , providing, therefore, additional thermodynamic driving force (pathway a, Scheme )…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As a matter of fact, regioselective cyclization of structurally related substrates such as 2‐alkynyl benzoic acid 26 , 2‐alkynyl benzamides 27 , propargyl ureas 28 , and propargyl guanidines 29 has been extensively studied and conditions have been established for performing either a 5‐ exo ‐dig or a 6‐ endo ‐dig cyclization (Figure ). However, the cyclization of amidine 19 has been far less investigated and to the best of our knowledge, only 5‐ exo ‐dig cyclization leading to imidazole is known . Indeed, in this case, the 5‐ exo ‐dig cyclization furnishes an aromatic compound 16 after facile double‐bond isomerization of the primary cyclization product 30 , providing, therefore, additional thermodynamic driving force (pathway a, Scheme )…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the loading of TfOH to 0.5 equiv,1 ,6dihydropyrimidine 17 a was formedi n7 8% isolated yield (entry 13). [30] It is worth noting that both Lavilla [21] and Hulme [31] have previously demonstrated that acid-catalyzedisocyanidei nsertion into the NH bond, while effective with anilines, failed with aliphatic amines.F inally,t ributylammonium triflate (nBu 3 NH + TfO À ), aw hite solid easily preparedf rom nBu 3 Na nd TfOH, was also able to catalyzet he [2+ +3] heteroannulationb etween 1a and 15 a (entry 14). On the other hand, tetrabutylammoniumt riflate was devoid of catalytic activity (entry 15).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[9] Thehomopropargyl amine 3a (R 1 = R 2 = Ph, R 3 = H) and tert-butyl isocyanide (4a)w ere chosen as test substrates (Scheme 2). [12] To our delight, reaction of 3a and 4a in toluene in the presence of AgOTf indeed afforded the proline amide 5a (16 %) resulting from aformal 1,1-gem difunctionalization of the terminal alkyne.Systematic survey of reaction conditions [*] Dr.S .T ong, [ varying the silver salt, the solvent, and the temperature allowed us to obtain 5a in 82 %y ield (d.r.1 :1) under the following optimized reaction conditions:AgOAc (0.1 equiv), toluene,4 0 8 8C, then FCC on SiO 2 (see the Supporting Information for details). [10] While many transition metals promote this transformation efficiently, [11] we have recently shown that as ilver salt, because of its high alkynophilicity,p referred to coordinate to the triple bond of the propargylamine,t herefore inhibiting the N À Hi nsertion process.…”
mentioning
confidence: 84%